Aplikasi Prediksi Kesehatan Menggunakan Machine Learning - Andry Meylani; Edi Surya Negara (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Based on data stated by the Ministry of Communication and Information, the level of use of mobile devices and the internet in Indonesia is very high. One application of mobile device technology is in the body health monitoring system. This health care monitoring system will help people monitor their health conditions to prevent and control chronic diseases and allow the medical team to monitor and assist when needed. In this study, a health prediction model and mhealth application were developed using one of the machine learning techniques, namely Naïve Bayes. Mhealth which has been integrated with machine learning can determine the possibility of individuals being healthy, moderately healthy, less healthy, and unhealthy. The body health prediction information data sent are in the form of body temperature, heart rate, systolic and diastolic blood pressure, respiration, and saturation, which are then displayed on a smartphone. With the help of the Health detection app, an individual can find out and deal with it at an early stage, to prevent the situation from getting worse